A two-photon fluorescent probe for selective methylglyoxal detection and application in living cells. Issue 6 (10th February 2015) - Tang, Tun; Zhou, Yimin; Chen, Yuqi; Li, Mengjun; Feng, Yan; Wang, Changcheng; Wang, Shaoru; Zhou, Xiang
Abstract : A novel two-photon fluorescent "turn-on" probe could detect methylglyoxal levels in living cells conveniently. Abstract : Methods based on fluorescent "turn-on" sensors have been developed for methylglyoxal (MGO) detection, but the two-photon one is hardly ever reported. In this study, a naphthalimide derivative PDN-1, which is a novel two-photon fluorescent "turn-on" probe for rapid and sensitive detection of methylglyoxal, is designed and synthesized. Under physiological conditions, the probe showed minimal background emission, whereas, after interacting with MGO, it exhibited significant fluorescence enhancement (33-fold) through the inhibition of the photoinduced electron transfer (PET) effect. The fluorescence enhancement showed a decent linear relationship with the MGO concentration ranging from 0 to 10 μM, with a detection limit of 77 nM. The mechanism of the PDN-1–MGO reaction was evaluated by 1 H, 13 C NMR spectroscopy and matrix-assisted laser desorption/ionization time-of-flight mass spectrometry. The specificity of PDN-1 for MGO to other aldehydes, ions, peroxide and nitric oxide is satisfactory. Imaging MGO in living cells by PDN-1 is also accomplished with high sensitivity and low cytotoxicity.